Implementasi Failover Dan Autoscaling Kontainer Web Server Nginx Pada Docker Menggunakan Kubernetes - Yosua Tito Sumbogo; Mahendra Data; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Web server is an important part used to provide website services. Web server is used to serve website requests for 24 hours 7 days if the web server is dead then the website service will not be used. The condition of web server that can not work or failure can be caused by some things like hardware malfunction, crash on web server, power outage, and network failure. NGINX is one of the web server software provider. NGINX is able to install on virtual server computers using container methods. this facilitates the deployment process because the containers are lightweight and portable. In order for the web server to serve requests it requires failover mechanism and autoscaling. Kubernetes is a software that has a Docker-based failover and autoscaling container mechanism. In this research the amount of hardware used is 3 servers that make up a cluster using Kubernetes, where 1 server will become master and 2 server as minion. From the research obtained the average time required for failover is 264.74s for node failure, and 3s for service failure. the average autoscaling time of the system requires 45s for scale up and 108s for scale down. Autoscaling Kubernetes is able to reduce CPU usage by 0.4%. The built system is capable of running web server with clustering method.